2008
DOI: 10.1021/la802839f
|View full text |Cite
|
Sign up to set email alerts
|

AFM Studies of the Effect of Temperature and Electric Field on the Structure of a DMPC−Cholesterol Bilayer Supported on a Au(111) Electrode Surface

Abstract: Atomic force microscopy (AFM) was used to characterize a phospholipid bilayer composed of 70 mol % 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) and 30 mol % cholesterol, at a Au(111) electrode surface. Results indicate that addition of cholesterol relaxes membrane elastic stress, increases membrane thickness, and reduces defect density. The thickness and thermotropic properties of the mixed DMPC-cholesterol bilayer supported at the gold electrode surface are quite similar to the properties of the mixed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 82 publications
6
64
2
Order By: Relevance
“…6A. The thickness of the film determined from force-distance curves was 5.1 AE 0.4 nm, which is in a very good agreement with the value reported by Chen and coworkers for the same systemwithin this potential range [49]. Upon the introduction of melittin, the changes in morphology of the bilayer were small during first 60 minutes.…”
Section: Dmpc/cholesterol Bilayer Vs 10 MM Melittinsupporting
confidence: 90%
“…6A. The thickness of the film determined from force-distance curves was 5.1 AE 0.4 nm, which is in a very good agreement with the value reported by Chen and coworkers for the same systemwithin this potential range [49]. Upon the introduction of melittin, the changes in morphology of the bilayer were small during first 60 minutes.…”
Section: Dmpc/cholesterol Bilayer Vs 10 MM Melittinsupporting
confidence: 90%
“…The thickness expected for a single bilayer composed of DMPC and cholesterol is ∼4.5 nm or even lower if the film is prepared by SUVs spreading. 21 Therefore, it is reasonable to assume that at this stage of adsorption some multilayered structure is formed on the electrode surface. On the other hand, it is still smaller than the thickness of the double bilayer.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Quite similar conclusions were drawn for a two-component system consisting of DMPC and cholesterol in a 7:3 molar ratio. 21 Interestingly, the studies of DMPC/cholesterol vesicles spreading on Au(111) with use of electrochemical scanning tunneling microscopy (EC-STM) revealed that at the early stages of film formation the molecules adsorb on the surface with a flat-lying orientation and separate into domains enriched with either DMPC or cholesterol. 22 Such an observation suggests that the mechanism of lipid vesicles spreading on Au(111) has to be stepwise and distinctly different from that observed on mica or other hydrophilic substrates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In order to increase the molecular-scale order in phospholipid bilayers obtained by vesicles spreading addition of cholesterol is necessary [9,11,32,88,126]. Phospholipid molecules in bilayers prepared by LB-LS transfer are closer packed, uniformly oriented, and show a higher degree molecular-scale order than lipid molecules in bilayers prepared by vesicles spreading [9,31,33,120,127,128]. Structural studies of potential induced chains in lipid bilayers prepared by vesicles spreading and LB-LS transfer were recently reviewed by Lipkowski [9].…”
Section: Application Of In Situ Pm Irras For the Determination Of Thementioning
confidence: 99%